Assessment of Hanging Type Grain Cleaner Drudgery Reducing Tool by Farm Women - Tripathi, S.P.; Chundawat, G.S.; Gour, Shashi; Somvanshi, S.P.S.; Singh, Kinjulck C. (Indian Journal of Extension Education, 2021)
The study was undertaken to assess ergonomically efficiency of hanging type wheatgrain cleaner, carried out in adopted villages under On Farm Testing (OFT) and FrontLine Demonstration (FLD) program conducted by KVK, Mandsaur (M.P.). Total Fifteen farmwomen were selected to assess the physiologicalworkload to compare the impact of improved technology over conventional practice for hanging type grain cleaner.Physiological parameters i.e. HR, energy expenditure, cardiac cost reduction and physiological cost reduction etc, were measured during operations. The results revealed that hanging type grain cleaner has proved proficient on time and output parameters. The average cardiac cost of work was decreased by 82.29 per cent while using hanging type grain cleanerfor wheat. Drudgery reduction was found 83.96 per cent and it saved timeby 89.10 per cent when compared to traditional practice. The physiological cost of work and energy expenditure in terms of heart rate were observed to be lower while performing activities with hanging type grain cleaner as compared to the traditional practice.